2020
DOI: 10.1155/2020/8833972
|View full text |Cite
|
Sign up to set email alerts
|

An Epithelial-Mesenchymal Transition (EMT) Preoperative Nomogram for Prediction of Lymph Node Metastasis in Bladder Cancer (BLCA)

Abstract: Lymph node (LN) metastasis is a lethal independent risk factor for patients with bladder cancer (BLCA). Accurate evaluation of LN metastasis is of vital importance for disease staging, treatment selection, and prognosis prediction. Several histopathologic parameters are available to predict LN metastasis postoperatively. To date, medical imaging techniques have made a great contribution to preoperatively diagnosis of LN metastasis, but it also exhibits substantial false positives. Therefore, a reliable and rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Logistic regression analysis was used to determine the predictive characteristics of preoperative lymph node metastasis. Considering that the pathological staging and detailed classification of TNM are more obtained by postoperative pathological examination than preoperative evaluation, in this study we included the StrLNM signature and mutation of C3orf70, which were proved to be obviously highly mutated in LN+ tumors when compared with LNtumors (Table S6) (19), as the candidate features to build the preoperative nomogram. Logistic regression found the StrLNM signature and C3orf70 mutation were statistically significant (p < 0.05) (Table S6).…”
Section: Individualized Prognostic Nomogram: Development and Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Logistic regression analysis was used to determine the predictive characteristics of preoperative lymph node metastasis. Considering that the pathological staging and detailed classification of TNM are more obtained by postoperative pathological examination than preoperative evaluation, in this study we included the StrLNM signature and mutation of C3orf70, which were proved to be obviously highly mutated in LN+ tumors when compared with LNtumors (Table S6) (19), as the candidate features to build the preoperative nomogram. Logistic regression found the StrLNM signature and C3orf70 mutation were statistically significant (p < 0.05) (Table S6).…”
Section: Individualized Prognostic Nomogram: Development and Validationmentioning
confidence: 99%
“…In recent decades, we have seen a shift from a single analysis of multiple biomarkers to the combinatorial analysis of a panel of biomarkers to construct markers, which is regarded as an useful and effectivetool for clinical management methods ( 18 ). Our team previously built a nomogram combining an EMT-LNM signature and somatic genetic mutations for prediction of LNM in BLCA which was pretty useful for clinical practice ( 19 ). And in the current study, we focused on TME patterns and tried to establish a nomogram which was centered on an StrLNM signature for preoperative prediction of LNM status in BLCA patients.…”
Section: Introductionmentioning
confidence: 99%
“…This process was induced by several EMT associated factors, such as the epithelial marker E-cadherin, the mesenchymal markers N-cadherin and vimentin, and the group of transcriptional repressors Zeb, SNAIL, Slug and Twist [30]. Accumulated evidences have revealed that EMT participates in tumor invasion and metastasis [28,31,32]. The reducing of E-caherin expression is one of signi cant EMT hallmark, as it's the crucial epithelial marker of EMT which distributed in epithelial cells junctions and participates in the composition of intercellular adhesion complex [28].…”
Section: Disscussionmentioning
confidence: 99%
“…This process was induced by several EMT associated factors, such as the epithelial marker E-cadherin, the mesenchymal markers N-cadherin and vimentin, and the group of transcriptional repressors Zeb, Snail, Slug and Twist (Cao et al, 2020b). Accumulated evidences have revealed that EMT participates in tumor invasion and metastasis (Cao et al, 2020a, Maruta and Greer, 1988, Zhou et al, 2019. The reducing of E-caherin expression is one of significant EMT hallmark, as it's the crucial epithelial marker of EMT which distrubuted in epithelial cells junctions and participates in the composition of intercellular adhesion complex (Zhou et al, 2019).…”
Section: Disscussionmentioning
confidence: 99%